Pengaruh Kinerja Keuangan, Leverage, dan Earning Volatility terhadap Volatilitas Harga Saham: Studi pada Perusahaan Sektor Teknologi di Bursa Efek Indonesia - Kayyana Ihsan Al Fatya; Sri Trisnaningsih (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Stock price volatility in the technology sector has become an important concern for investors due to the sector’s high uncertainty, rapid business transformation, and sensitivity to economic changes. Understanding the financial factors that influence stock price fluctuations is therefore essential for improving investment decision-making and risk assessment. This research investigates the influence of financial performance, leverage, and earning volatility on the stock price volatility of technology companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative causal approach was employed using secondary data obtained from annual financial statements and stock market data. The sample consisted of 23 technology companies selected through purposive sampling, resulting in 69 observations. Multiple linear regression analysis was applied after fulfilling the classical assumption tests. The findings indicate that financial performance, proxied by Return on Assets (ROA), has a negative but insignificant relationship with stock price volatility, while leverage, measured by Debt to Equity Ratio (DER), shows a positive but insignificant effect. In contrast, earning volatility demonstrates a positive and statistically significant influence on stock price volatility. Simultaneously, the three independent variables significantly affect stock price volatility, although the explanatory power of the model remains relatively limited. These findings provide additional empirical evidence regarding signaling theory in the context of emerging capital markets and highlight earning volatility as a key consideration for investors when evaluating technology-sector stocks characterized by high uncertainty and dynamic business environments.